2004
DOI: 10.1158/1078-0432.ccr-03-0581
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of c-kit Mutation in Localized Gastrointestinal Stromal Tumors

Abstract: Purpose: Constitutive mutational activation of c-kit has been found to be associated with the pathogenesis of gastrointestinal stromal tumors (GISTs). The prognostic significance of c-kit mutations, however, is still controversial.Experimental Design: We examined 86 patients curatively resected for localized GIST. Genomic DNA was extracted from paraffin-embedded tumor tissues. Exons 9, 11, 13, and 17 of the c-kit gene were amplified by PCR and sequenced.Results: Mutations in exon 11 were detected in 61 tumors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
2
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 21 publications
3
102
2
5
Order By: Relevance
“…Although KIT exon 11 mutations have been reported in GISTs from different locations from esophagus to anus, [105][106][107][108][109][110][111][112] duplications showed strong predilection to gastric location; 59 of 67 (88%) reported GISTs with KIT exon 11 duplications originated from stomach. 61,74,76,77,83,84,97,101,113 …”
Section: Kit Regulatory Domain Mutations (Exon 9 Exon 11)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although KIT exon 11 mutations have been reported in GISTs from different locations from esophagus to anus, [105][106][107][108][109][110][111][112] duplications showed strong predilection to gastric location; 59 of 67 (88%) reported GISTs with KIT exon 11 duplications originated from stomach. 61,74,76,77,83,84,97,101,113 …”
Section: Kit Regulatory Domain Mutations (Exon 9 Exon 11)mentioning
confidence: 99%
“…74,81,101 Technical problems limiting detection of duplications in FFPE tissues may contribute to this discrepancy, since other studies from Korea and China have been reported KIT exon 11 duplications in GISTs. 83,84,99,100 …”
Section: Frequency Of Kit and Pdgfra Mutationsmentioning
confidence: 99%
“…Polymerase Chain Reaction and Sequencing of KIT and PDGFRA Amplification and direct DNA sequencing of KIT exons 9, 11, 13, and 17 and PDGFRA exons 12 and 18 were performed according to previously described procedures [2,14]. Patient samples negative for KIT or PDGFRA mutations were subsequently amplified with primers specific for KIT exons 8, 14, and 15 followed by direct DNA sequencing [18,19].…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…5,6,8,[12][13][14][15][16][17][18][19][20][21][22][23] All analyzed duplications, except two (2.1%), have been reported in the KIT region c.1729_1794 (g.75722_75787). Primers CK11.1F and CK11.3R closely flanking this region were used for PCR amplification of smaller products, yielding 129 bp in KIT-WT.…”
mentioning
confidence: 99%